Optimalisasi Lahan Sekolah Untuk Mewujudkan Sekolah Pangan di Sekolah Menengah Atas Negeri 1 Kedungwuni Kabupaten Pekalongan - Badrudin, Ubad; Pradana, Candra Dwi; Nugraha, Deril Eka Dava; Fauziah, Fifin; Taqwa, Muhammad; Ma’arif, Samsul; Ramadhani, Farchan Mushaf Al Ramadhani; Madusari, Benny Diah; Sajuri, Sajuri; Supriyanto, Eka Adi; Afiatan, Arbina Satria; Arifin, Imam (Jaanur ElBarik Indonesia, 2025)
The purpose of this community service activity is to provide information and knowledge about crop cultivation techniques that can produce food and serve as a food source. The activity was carried out from Monday, April 21, 2025, to Tuesday, June 4, 2025, using dissemination and socialization methods about the benefits of food crops and food crop cultivation techniques. The results of the community service showed that all participants were enthusiastic and excited to participate in the entire series of activities, as evidenced by their attentiveness and participation until the end of the event. There was also a significant change in their knowledge of crop cultivation, which was 27% before the dissemination and cultivation practices, but increased to 93% after the dissemination and cultivation practices. These results were obtained from pre-test and post-test assessment forms filled out by the extension participants.